Effect of Selective Temporary Anaesthesia in Combination with Sensory Re-Education on Improvement of Hand Sensibility after Median and Ulnar Nerve Repair - Roghayeh Hasan-Zadeh; Ahmad Reza Roofigary; Akram Azad; Laleh Lajevardi; Mohammad Reza Keyhani (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: The results of sensory improvement from nerve repair in adult are often poor. To confirm with previous results and this hypothesis that forearm deafferentation would enhance the sensory outcome by increasing the cortical hand representation, this study is aimed to investigate the effect of repeated sessions of cutaneous forearm anaesthesia of the injured limb, in combination with sensory re-education on the sensory outcome in the hand after median or ulnar nerve repair. Materials & Methods: This experimental study was designed as a double-blind randomized clinical trial. 13 patients that they had been undergoing surgery of hand nerves repaire were selected probability and assigned to examination (n=6) and control (n=7) group. During a 2 week period, a topical anaesthetic cream (Lidocaine) for examination group and a placebo for control group was applied repeatedly (twice a week) for 1 hour onto the flexor aspect of the forearm of injured hand and combined with sensory re-education. Assessments of sensory function were performed prior to the experiment and after the fourth application of Lidocaine/placebo. For analysis of data, Wilcoxon singed rank and Mann - Whitney U-tests were used. Results: Perception of touch that was measured with SWMs, had been improved significantly in the Lidocaine group in comparison with placebo group (P=0/03). Conclusion: This finding suggests that forearm deafferentation of injured limb, in combination with sensory re-education, can enhance sensory reover after nerve repair.